EPA standby facility for capacity building : managed by a Steering Committee comprising representatives of the European Commission and CARICOM Secretariat ([S.l.] [s.n.])
Presents information on the facility financed by the EU and administered by the Caribbean Development Bank, one of the seven components of the EU-funded 10th EDF project titles 'Support to the Caribbean Forum of the ACP State (CARIFORUM in the implementation of the commitments undertaken under the EPA.'
Keywords: CAPACITY BUILDING